Object Surface Recognition Based on Standing Waves in Acoustic Signals - Kumon, Makoto; Fukunaga, Rikuto; Manabe, Tomoya; Nakatsuma, Kei (Frontiers in Robotics and AI, 2022)
This paper proposes the use of the standing waves created by the interference between transmitted and reflected acoustic signals to recognize the size and the shape of a target object. This study shows that the profile of the distance spectrum generated by the interference encodes not only the distance to the target, but also the distance to the edges of the target surface. To recognize the extent of the surface, a high-resolution distance spectrum is proposed, and a method to estimate the points on the edges by incorporating observations from multiple measurement is introduced. Numerical simulations validated the approach and showed that the method worked even in the presence of noise. Experimental results are also shown to verify that the method works in a real environment.